COMMUNITY SOCIAL ACTION ON PUNDHEN LO SARI CREATIVE PARK IN MAOSPATI VILLAGE MAGETAN REGENCY - Kusnul Khotimah; Katon Setyawan; Sarmini Sarmini; Nasution Nasution (Jurnal Partisipatoris, 2023)
The development of religious tourism does not have to be related to mystical or sacred things. But it can be developed into a creative park with open facilities for children to play. As happened in the Maospati Magetan Village, it has succeeded in developing a village pundhen which was originally a wingit (sacred) place which was converted into an open (profane) park, named Park Creation Lo Sari Maospati. However, this creative park is still used as an annual village clean location by the community. The theory used by the researcher as a research reference in this study is the theory of action from Max Weber, because the researcher sees the phenomenon of the development of the Lo Sari creation park in an effort to empower social and spiritual economy, which is very relevant to the theory of action from Max Weber. This research approach uses a qualitative approach with a Schutz phenomenological perspective. The results of the study indicate that there are at least three groups of people who can be analyzed for their social actions. First, community groups with instrumental rational action, such as village officials and Pokadrwis. They assume that the development of Lo Sari's Pundhen into a creative park will increase the income of local residents. The second group is value rational action, almost the same as instrumental rational action group, except that this group prioritizes religious values. While the third is a traditional action, where the actors who carry out activities at Pundhen Lo Sari are those who follow their previous parents.